Factors Affecting Non-Performing Financing in Islamic Rural Banks: A Case Study of selected East Java Province - Sapta, Andriyan Eka (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study aims to analyze the significance of the influence of Financing to Deposit Ratio, Operational Costs to Operational Income, Capital Adequacy Ratio, Gross Domestic Product, and BI-Rate on Non-Performing Financing at Islamic Rural Banks in East Java for the 2020–2023 period, either simultaneously or partially. The sample in this study were 22 (twenty-two) Islamic Rural Banks in East Java, which were selected using a purposive sampling technique. The analysis model used in this study is a panel data regression analysis model. The results of proving the hypothesis and discussion show that the Financing to Deposit Ratio, Operational Costs to Operational Income, Capital Adequacy Ratio, Gross Domestic Product, and BI-Rate simultaneously have a significant effect on Non-Performing Financing. Furthermore, Financing to Deposit Ratio partially has a positive but not significant effect on Non Performing Financing, Operational Costs to Operational Income and Gross Domestic Product partially has a positive and significant effect on Non-Performing Financing, Capital Adequacy Ratio partially has a negative significant on Non Performing Financing, and BI-Rate partially has a negative but not significant effect on Non-Performing Financing at Islamic Rural Banks in East Java for the 2020–2023 period.